2017
DOI: 10.1038/s41598-017-18078-3
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Contraceptives Differentially Suppress TFV and TAF Inhibition of HIV Infection and TFV-DP in Blood and Genital Tract CD4+ T cells

Abstract: HIV prevention research is focused on combining antiretrovirals (ARV) and progestin contraceptives to prevent HIV infection and pregnancy. The possibility that progestins compromise ARV anti-HIV activity prompted us to evaluate the effects of progestins on tenofovir (TFV) and TFV-alafenamide (TAF) on HIV infection and intracellular TFV-diphosphate (TFV-DP) concentrations in blood and genital CD4+ T cells. Following incubation of blood CD4+ T cells with TFV or TAF, Medroxyprogesterone acetate (MPA), but not Lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 55 publications
(92 reference statements)
1
22
0
Order By: Relevance
“…Blood from women was obtained from our IRB-approved Blood Donor Program at Dartmouth-Hitchcock Medical Center. CD4+ T cells were purified with the CD4+ T cell isolation kit (Miltenyi Biotech) from frozen peripheral blood mononuclear cells (PBMC) as described before 5,8 . Purified blood CD4+ T cells were activated in vitro using X-vivo 15 media (Lonza, Walkersville, MD) with Phenol Red plus Phytohemagglutinin (PHA, 2.5 µg/ml; Sigma, St Louis, MO) and IL-2 (50 U/ml, AIDS Research and Reference Reagent Program, Division of AIDS, NIAID, NIH: Human rIL-2 from Dr. Maurice Gately, Hoffmann- La Roche Inc.) for 24 hr as described previously 5,8 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood from women was obtained from our IRB-approved Blood Donor Program at Dartmouth-Hitchcock Medical Center. CD4+ T cells were purified with the CD4+ T cell isolation kit (Miltenyi Biotech) from frozen peripheral blood mononuclear cells (PBMC) as described before 5,8 . Purified blood CD4+ T cells were activated in vitro using X-vivo 15 media (Lonza, Walkersville, MD) with Phenol Red plus Phytohemagglutinin (PHA, 2.5 µg/ml; Sigma, St Louis, MO) and IL-2 (50 U/ml, AIDS Research and Reference Reagent Program, Division of AIDS, NIAID, NIH: Human rIL-2 from Dr. Maurice Gately, Hoffmann- La Roche Inc.) for 24 hr as described previously 5,8 .…”
Section: Methodsmentioning
confidence: 99%
“…CD4+ T cells were purified with the CD4+ T cell isolation kit (Miltenyi Biotech) from frozen peripheral blood mononuclear cells (PBMC) as described before 5,8 . Purified blood CD4+ T cells were activated in vitro using X-vivo 15 media (Lonza, Walkersville, MD) with Phenol Red plus Phytohemagglutinin (PHA, 2.5 µg/ml; Sigma, St Louis, MO) and IL-2 (50 U/ml, AIDS Research and Reference Reagent Program, Division of AIDS, NIAID, NIH: Human rIL-2 from Dr. Maurice Gately, Hoffmann- La Roche Inc.) for 24 hr as described previously 5,8 . Activated CD4+ T cells were plated at a density of 1 × 10 5 cells per well in round-bottom 96-well culture plates (Corning, Corning, NY) in 0.1 ml of Immune cell media consisting of X-vivo 15 Media supplemented with Phenol Red and 10% human AB serum (Valley Biomedical, Winchester, VA) prior to treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, 100% of rhesus macaques treated with depot medroxyprogesterone acetate to mimic hormonal contraception and TDF + FTC PrEP remained uninfected after 20 vaginal challenges with SHIV . However, in vitro analysis of CD4 cells isolated from the female genital tract and treated with depot medroxyprogesterone acetate, levonorgestrel, or norethisterone revealed reduced formation of TFVdp and its anti‐HIV activity in the depot medroxyprogesterone acetate treatment group following TFV treatment, but not for a similar prodrug, tenofovir alafenamide . One exploratory analysis of data from the MTN001 trial (a 7‐site, open‐label, 3‐period crossover PK study of oral and topical dosing) found that using any type of hormonal contraceptives (administered as oral or injectable) was associated with a 27% to 73% decrease in TFVdp concentrations in PBMCs from HIV‐uninfected women .…”
Section: Role Of Sex Hormones In Regulating Drug Efficacy In the Femamentioning
confidence: 98%
“…85 However, in vitro analysis of CD4 cells isolated from the FGT and treated DMPA, levonorgestrel, or norethisterone revealed reduced formation of TFVdp and its anti-HIV activity in the DMPA treatment group following TFV treatment but not for a similar prodrug, tenofovir alafenamide (TAF). 86 One exploratory analysis of data from the MTN001 trial (a 7-site, open label, 3 period crossover PK study of oral and topical dosing) found that using any type of hormonal contraceptives (administered as oral or injectable) was associated with a 27–73% decrease in TFVdp concentrations in peripheral blood mononuclear cells (PBMCs) from HIV uninfected women. 87 However, the post hoc nature of this analysis precluded controlling for potential confounders such as geographical differences in hormonal contraceptive prescribing patterns and adherence rates among the 4 US and 3 African sites.…”
Section: Role Of Sex Hormones In Regulating Drug Efficacy In the Femamentioning
confidence: 99%
“…Additionally, DMPA has been associated with increased risk of HIV infection [5]. In vitro, coincubation of CD4 + T cells with medroxyprogesterone acetate decreased TFV-DP concentrations and protection from HIV infection [6]. Therefore, we sought to determine whether DMPA decreased TFV-DP FGT exposure, potentially compromising PrEP efficacy.…”
mentioning
confidence: 99%